A Comprehensive Synthesis of Technology Adoption Models in the Context of QRIS Digital Payment in Indonesia: A Systematic Review of UTAUT, TAM, and TRAM - Diah Widiawati; Yosanda Zata Aman; Burhanuddin Jauhari (University of Merdeka Malang, 2026)
This Systematic Literature Review (SLR) provides a comprehensive synthesis of technology adoption models (TAM, UTAUT, TRAM) in the context of QRIS digital payment in Indonesia, aiming to resolve the theoretical fragmentation in existing literature. The study strictly adhered to the PRISMA protocol, examining Scopus-indexed articles from 2022 to 2025. The synthesis, predominantly based on quantitative studies utilizing PLS-SEM , reveals a strong convergence: Perceived Usefulness/Performance Expectancy and Trust consistently emerge as the most significant determinants of behavioral intention and actual QRIS adoption among both consumers and MSMEs. A critical divergence noted is the varying significance of Habit for sustained use and the pivotal role of contextual factors, such as Central Bank policies and the COVID-19 pandemic, which are often overlooked in traditional frameworks. Practically, the findings underscore the need for FinTech providers to prioritize investments in transparent security protocols and the clear communication of QRIS benefits. Future research is urged to employ longitudinal studies and cross-sectional comparisons between user segments to build a more integrated, parsimonious meta-model of digital payment acceptance.